Phase I Trial Using Induction Ciplatin, Docetaxel, 5-FU and Erlotinib Followed by Cisplatin, Bevacizumab and Erlotinib With Concurrent Radiotherapy for Advanced Head and Neck Cancer. (May 2018) - Ahn, Peter H.; Machtay, Mitchell; Anne, Pramila R; Cognetti, David; Keane, William M.; Wuthrick, Evan; Dicker, Adam P.; Axelrod, Rita S.
Abstract : Objectives: Bevacizumab (avastin) and erlotinib (tarceva) had shown early clinical activity against head and neck cancer (HNC). We initiated a phase I trial of induction cisplatin, docetaxel, 5-fluorouracil and erlotinib (TPF-E) followed by cisplatin, bevacizumab and erlotinib (PA-E) with radiotherapy (XRT) for advanced HNC. The goal was to determine maximum tolerated erlotinib dose. Methods: Eligible patients had stage IVA or higher HNC with good performance status, hematologic, and renal reserve. Two cycles of induction TPF-E were administered. XRT was administered with concurrent weekly cisplatin and bevacizumab every 2 weeks. Initial erlotinib dose was 50 mg daily from start of induction chemotherapy until radiotherapy completion. Erlotinib dose escalations to 100 and 150 mg were planned. Results: Thirteen patients with previously untreated locoregional disease (11 patients) or oligometastatic (2 patients) HNC were enrolled. Totally, 11 of 13 patients completed XRT as planned. Four of 8 patients in cohort 1 (erlotinib 50 mg), 3 of 4 patients in cohort 2 (100 mg), and 0 of 1 patients in cohort 3 (150 mg) completed the regimen. Two patients had significant gastrointestinal complications (bleeding and perforation), and 1 had dose-limiting diarrhea. Maximum tolerated dose was reached at 50 mg erlotinib. At median 23.4 months follow-up, 5 patients (38%) have no evidence of disease, and 2 (15%) have stable but measurable disease. Conclusions: Erlotinib in combination with induction TPF followed by erlotinib, cisplatin, and bevacizumab with XRT is active but toxic. Gastrointestinal toxicities partly caused high rates of study withdrawal. All doses studied in this protocol caused unexpected toxicities and we do not recommend advancement to phase II.